Application and Performance of Google Forms for Online Data Collection and Analysis: A Case of North Eastern Region of India (Indian Journal of Extension Education, 2015)
Google is a worldwide recognized search engine. It also provides internet related services and products to a wide range of users at greater utility and lesser cost. Google also launched web based applications like Google docs, Google forms, Google drive, Google slides, Google sheets, etc., which has immense potential for increasing productivity of academicians, researchers, students, professionals and policy makers, etc. Among the above mentioned web based applications, Google forms is one of the most important tools having great relevance to social science in general and data collection methodology in particular. To study the feasibility and performance of Google forms in KVKs of North Eastern region, i.e. Zone-III, three pilot tests were taken to collect data. The online forms were created and online data were collected for various projects and activities of the ATARI Zone-III, Umiam, Meghalaya. The outcomes depicted that in eight North Eastern States, the success of data collection and response rate is more than the traditional and manual way of data collection. All KVKs connected with stable internet connection were able to feed and submit data. The responses increased tremendously when respondents were systematically targeted. Thus, Google forms can significantly make difference to collect online data from respondents who are connected with internet. In order to collect data from respondents who don’t have access to the internet (ex. Marginal farmers, tribal and rural populations) researchers can use smartphones or tablet-PCs to collect real time data with greater speed. It will save the paper time and manual efforts of researchers. The non-tampered analysis of survey with fullest authenticity is also possible within few seconds without any manual tabulation and coding. Hence, Google form is a boon for enhancing research productivity of scholars of the National Agricultural Research System.